Association of doxycycline use with the development of gastroenteritis, irritable bowel syndrome and inflammatory bowel disease in Australians deployed abroad. Issue 8 (6th August 2013) - Lee, T. W.; Russell, L.; Deng, M.; Gibson, P. R.
Abstract: Background: The risks are unknown for developing chronic gastrointestinal illness when personnel are relocated short term to other countries and when taking antibiotic prophylaxis in areas where malaria is endemic. Aim: To examine the associations of deployment to developed or developing countries and exposure to doxycycline with the new onset of acute gastroenteritis, irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). Methods: A cross‐sectional web‐based survey of all current and past members of the Australian Federal Police Association was undertaken. Independent predictors of gastrointestinal illness were examined by logistic regression analysis relative to those not deployed without exposure to doxycycline. Results: Of 1300 respondents (response rate 34%), 133 were excluded due to pre‐existing chronic gastrointestinal illness. Five hundred and ninety had episodes of overseas deployment for a median duration of 6.5 (range 0.1–149) months. Eighteen (3%) of those not deployed took doxycycline compared with 171 (30%) of those deployed. The risk of acute gastroenteritis was associated with deployment itself without clear association with doxycycline. Doxycycline exposure was associated with increased onset of IBS in those deployed to developing (odds ratio [OR], 6.99; 95% confidence interval [CI], 3.19–15.31) and developed country (OR, 6.93; 95% CI, 1.40–34.39). New onset of IBD (1.5%) was associated with deployment to developed countries and with doxycycline exposure (OR, 8.75; 95% CI, 1.67–45.86)). Conclusions: The use of doxycycline is a risk factor for developing IBS and possibly IBD when deployed to developing and developed countries respectively. Doxycycline as a risk factor for chronic gastrointestinal illness warrants a prospective large‐scale study.